An Activity Theory Approach to Moderation for Fair Assessment in Transnational Education - Thuraisingam, T.; Sanderson, G.; Mahmud, S.; Yeo, S.; Briguglio, Carmela; Wallace, M.; Hukam Singh, P. (Australian Learning & Teaching Council, 2010)
This paper presents research from an Australian Learning and Teaching Council (ALTC) priority project which focuses on the assessment moderation practices between Australian and transnational partner universities. This paper addresses the challenges faced by transnational academic staff in ensuring comparable assessment standards. The data illuminates many issues of culture, language, relationships, trust, power and control. Using activity theory and its principles of contradictions, these issues are analyzed in terms of Engestrom's expanded mediated triangle. The components of subject, mediating tools, objects, rules, community and division of labor are interconnected and in constant dynamic interaction emphasizing the social and contextualized nature of moderation practices and policies. Systemic tensions are bound to emerge between and among these components. This paper sets out to identify these systemic tensions or contradictions for their heuristic value andpotential as the driving force for change, indicating points of intervention to improve assessment moderation practices and policies. Among the three indicated contradiction triads, some fundamental secondary contradictions exist between subject-community-object, subject-mediating tools-object and subject-division of labor-object. These help identify the weaknesses in the existing collaborative pattern, lack of efficacy of the mediating tools for ignoring the 'culture of use' of the tools anda clear understanding of roles and responsibilities on the ground.